A new, simple three-step method for determining gestational age - Tunçer, Müyesser; Yılgör, Esat; Erdem, Gülşen (The Turkish Journal of Pediatrics, 1982)
A new, simple three-step method for determining gestational age is presented. The usefulness of facial appearance, as a new criterion for differentiating infants with fetal malnutrition from prematures, is emphasized. Besides the accuracy of this method (r = 0.945), simplicity in application, good correlation of results obtained by different members of the neonatal unit and other advantages are discussed.